Les faits divers - Jean-Claude Picard (Communication)
The news termed « in-brief » has come, over several decades, to occupy a larger and larger space with in Québécois media. This research project, based on a sample from the daily newspapers La Presse and Le Soleil, allows, for the first time, a concrete measure of this evolution, from 1945 to 1995. The conclusion is that in fact, space allocated to photographs and texts of news-in-brief segments has augmented steadily throughout this period, particularly on pages one and three of these two newspapers. Moreover, it is concluded that the news-in-brief segments are now focussed on violent acts more than on any other type of news.